Adaptation and propagation of classical swine fever virus in different cell lines - MEDHI, P; SARMA, D K; SARMAH, R (The Indian Journal of Animal Sciences, 2012)
Adaptation and propagation of 10 classical swine fever virus (CSFV) field isolates and the lapinized vaccine strain of CSFV were made in PK-15 and PS cell lines. None of the field isolates and the vaccine strain could be adapted in MDBK cell line. Four field isolates of CSFV produced cytopathic effect in both the cell lines. All the field isolates and the vaccine strain were propagated in both the cell lines up to fifth passage level after the initial adaptation. A gradual increase of the viral antigen based on the OD value in sandwich ELISA test was observed from the first to the fifth passages in the cell lines. The OD value of the virus isolates in the PK-15 cell line ranges from 0.612 to 1.538 and in the PS cell line ranges from 0.703 to 1.742 at fifth passage level. The log TCID50 of the virus isolates in the PK-15 cell line varies from 2.75 to 6.25 and in the PS cell line ranges from 2.25 to 6.50 at the fifth passage level. Although no statistically significant differences in the OD values and the logTCID50 values of the virus isolates and the vaccine virus strain was observed in the PK-15 and PS cell lines, but the use of PS cell line for adaptation and propagation of CSFV is the first report and this cell line appears to be one of the best alternatives of PK-15 cell line for propagation of CSFV.